Disfemisme dalam Akun Facebook Kementerian Kesehatan RI Tentang Virus Corona - Fira Nurul Hidayah; Muhammad Mukhlis (UIR Press, 2023)
This study aims to describe the forms and functions of dysphemism used by netizens in comments on the Indonesian Ministry of Health's Facebook account about the corona virus. This study uses a qualitative research approach with descriptive methods obtained through observation of existing data. The results of the study show that many netizen comments use dysphemism with the most frequently used forms of language being word, phrase, and expression dysphemism. There are 35 linguistic forms of dysphemism found in this study. The function of dysphemism consists of five functions, namely as a sign of anger, a means of criticizing, a means of satirizing, a means of insulting, and a means of declaring taboo or obscene things. This research was conducted in May, June, July and August 2021 using the research object of netizen comments. As a qualitative researcher, the researcher becomes a key instrument and must have extensive theoretical knowledge and insight to obtain accurate research results.